Coagulation parameters are associated with the prognosis of immunoglobulin a nephropathy: a retrospective study - Xia, Ming (BMC Nephrol, 2020)
BACKGROUND: Interstitial fibrosis/tubular atrophy (T) score is a known determinant of the progression of immunoglobulin A nephropathy (IgAN). Strong evidence indicates that the components of the coagulation system closely linked with fibrotic events have been highlighted in the kidney. However, whether the coagulation system can affect the renal outcome of IgAN remains unclear. Herein, we investigated the association of coagulation parameters and pathological phenotype of IgAN and their combined effects on the deterioration of renal function. METHODS: This retrospective study included N = 291 patients with biopsy-proven IgAN from May 2009 to April 2013 in the Second Xiangya Hospital. Clinical data, pathological features were collected, and the associations of coagulation parameters at biopsy, T score, and renal outcome were evaluated. T score indicated the degree of tubular atrophy or interstitial fibrosis. The renal outcome was defined as an end-stage renal disease (ESRD) or an irreversible 50% estimated glomerular filtration rate (eGFR) reduction. RESULTS: Shorter prothrombin time (PT) and the activated partial thromboplastin time (APTT) were significantly associated with T (both p < 0.001). PT (< 11.15 s) or APTT (< 29.65 s) had worse cumulative survival rate (p = 0.008, p = 0.027 respectively) and were significantly but not independently associated with a higher risk of renal outcome (p = 0.012, p = 0.032 respectively). In the combined analyses of PT, APTT, and T lesions, the odd ratios for the outcome were significantly higher in the presence of T with PT (< 11.15 s) or APTT (< 29.65 s). CONCLUSION: Shorter PT and APTT are associated with an increased incidence of the T lesion and are additional factors that portend a poorer prognosis in IgAN. Monitoring coagulation function might be important when assessing the risk of progression. Additional studies exploring the molecular mechanism between coagulation and IgAN pathology are needed.